The Effect of Economic Value Added, Market Value Added, Operating Leverage and Dividend Policy on Stock Returns in Coal Subsector Mining Companies Listed on the Indonesia Stock Exchange for the 2014-2019 Period - Lestari, Riska Devi; Sriyono, Sriyono (Universitas Muhammadiyah Sidoarjo, 2021)
This study was conducted to analyze the effect of Economic Value Added (EVA), Market Value Added (MVA), Operating Leverage and Dividend Policy on Stock Returns in Coal Subsector Mining Companies Listed on the Indonesia Stock Exchange for the 2014-2019 Period. The data collection technique used is using the purposive sampling technique and the number of samples used is 11 companies. The variables used in this research are Economic Value Added (EVA), Market Value Added (MVA), Operating Leverage and Dividend Policy as independent variables and stock return as dependent variable. The analytical method used is multiple linear regression analysis. The results of this study indicate that Economic Value Added (EVA) has a significant positive effect on stock returns, Market Value Added (MVA) has a significant negative effect on stock returns, Operating Leverage has no significant positive effect on stock returns and Dividend Policy has a significantly positive effect on stock returns.